2020
DOI: 10.1164/rccm.202001-0077le
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Crystalloids in Sepsis: Are We There Yet?

Abstract: We read the post hoc analysis of the SMART (Isotonic Solutions and Major Adverse Renal Events Trial) trial with great interest,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Most clinical evidence of the interaction between fluids and vasopressors comes from trials defining fluid administration relative to vasoactive exposure (30,31,39,40). In an openlabel trial of 99 patients, restricted volume therapy (defined as vasopressor commencement for MAP < 65 mm Hg after 1,000 mL IV fluids) showed no difference in mortality when compared with usual care (75).…”
Section: Clinical Evidence Of Interplaymentioning
confidence: 99%
See 2 more Smart Citations
“…Most clinical evidence of the interaction between fluids and vasopressors comes from trials defining fluid administration relative to vasoactive exposure (30,31,39,40). In an openlabel trial of 99 patients, restricted volume therapy (defined as vasopressor commencement for MAP < 65 mm Hg after 1,000 mL IV fluids) showed no difference in mortality when compared with usual care (75).…”
Section: Clinical Evidence Of Interplaymentioning
confidence: 99%
“…Balanced crystalloids are more physiologic than sodium chloride, though the hypotonicity and buffering capacity of lactated ringers and potential for hypotension from acetate in plasmalyte-A may be concerns in specific patients with septic shock (28,29). Studies within the critically ill have shown lower risk of in-hospital or 30-day mortality, AKI, or major adverse kidney event in the first 30 days with the use of balanced crystalloids over sodium chloride solutions (MAKE30) were lower, even at low fluid volumes (1.5 L resuscitative fluid) (28)(29)(30)(31)(32). Unless patient-specific contraindications exist, a balanced crystalloid should be provided for IVF resuscitation in sepsis and septic shock.…”
Section: Choice Of Ivfmentioning
confidence: 99%
See 1 more Smart Citation